2014
DOI: 10.7202/1025028ar
|View full text |Cite
|
Sign up to set email alerts
|

From “Canadians First” to “Workers Unite”: Evolving Union Narratives of Migrant Workers

Abstract: Résumé de l'articleRésuméAu début des années 2000, des changements dans la politique du gouvernement fédéral canadien ont conduit à une croissance rapide du Programme des travailleurs étrangers temporaires (TÉT), grâce à une augmentation du nombre de professions éligibles. Auparavant, peu d'organisations syndicales au Canada entretenaient de liens avec les TÉT, mais avec la promulgation de ces nouvelles règles et le débat politique qu'elles ont déclenché, les syndicats se sont vus, pour la première fois, confr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Union leaders' public rhetoric to the influx of TFWs has been mixed. Foster (2014) finds union spokespersons initially emphasized a 'Canadians First' approach, arguing TFWs undermined working conditions but under the shifting political context began expressing concern over mistreatment of TFWs. The evolving narrative suggests unions have been conflicted over TFWs.…”
Section: Canadian Unions and Migrant Workersmentioning
confidence: 99%
“…Union leaders' public rhetoric to the influx of TFWs has been mixed. Foster (2014) finds union spokespersons initially emphasized a 'Canadians First' approach, arguing TFWs undermined working conditions but under the shifting political context began expressing concern over mistreatment of TFWs. The evolving narrative suggests unions have been conflicted over TFWs.…”
Section: Canadian Unions and Migrant Workersmentioning
confidence: 99%
“…Foster (2014; see also Foster et al, 2015) studied the response of Canadian unions to TFWs and identified three temporally sequential approaches or narrative arcs. The first, beginning in 2006 when the influx of TFWs was rapidly increasing, was reactive and negative, denying there were local labour shortages and demonizing employers for using TFWs to drive down wages and avoid unions.…”
Section: The Changing Landscape Of Migrant Worker Programs In Canadamentioning
confidence: 99%
“…Notwithstanding the above, it would be overly simplistic to characterize the response of the Canadian workers and union organizers as reactive and negative, to use the categories developed by Foster (2014). Organizers also perceived that the Vietnamese workers were being exploited and paid significantly less than the Canadians and could benefit from being unionized.…”
Section: The Cs Wind Storymentioning
confidence: 99%
“…We specifically wanted to identify what strengths and limitations were observed regarding CSO engagement with labor issues, what governance mechanisms (if any) were discussed in relation to labor, and what roles CSO actors or groups had. An analysis of the literature that focuses on labor within the food system, particularly from a North American perspective, reveals several focus areas, notably migrant labor policy such as the Seasonal Agricultural Worker Program (SAWP; McLaughlin and Weiler, 2017;Weiler et al, 2017); health and safety of migrant workers (Preibisch and Otero, 2014;Weiler and McLaughlin, 2019;Weiler and Grez, 2022); migrant worker residency status, worker education, and worker organizing (Grez, 2006;Jayaraman, 2014;Perry, 2019); labor exploitation (Coplen, 2018;Klassen et al, 2022;Reese and Sbicca, 2022); and collective bargaining and unionization (Foster, 2014;Hall, 2015;Sbicca, 2015). Much of the literature identified migrant labor and specifically migrant farm labor.…”
Section: Introductionmentioning
confidence: 99%